ROLE OF ATTITUDE AND VALUE ON BEHAVIORAL INTENTION OF YOUTH TOWARDS ADOPTION OF SOLAR PANELS - Sharma, Mrs. Neetu; Kumari R, Dr Oum (The journal of contemporary issues in business and government, 2022)
Energy plays a very important role in the process of attaining economic growth and development. But the price to be paid for this development is very huge as more than 70 % of energy needs in our economy is met from fossil fuel which is adversely affecting our environment. Despite huge solar potential in our country we are unable to tap it. The total solar potential for India is estimated as 750 GW (MNRE) but the current solar power installed capacity is just 3 GW. This clearly brings out the fact that to protect our planet without compromising the development goals we need to rigorously consider the tapping of solar potential. This would help us to fight the problems like Global warming and climate change. The present article is an attempt to investigate the measure to optimize solar power in future. This could not happen without bringing a change in the attitude and behavior of the people. To bring a change in the attitude and behavior of consumers we need to emphasize on creation of habits through values. The cross- sectional data from 165 students’ samples using structured questionnaire in Jaipur city is used in this study. The reason for selecting students as respondents for the study is that today youth have more awareness about environment, global warming, and the importance of green products. It also evidenced that the consumer’s positive attitude along with the behavior towards environment, awareness of the eco-friendly products and value of the (solar panels) is satisfactory then the consumers have positive behavioral intention to adopt the solar panels. The results of the study could help us to develop effective marketing strategies for solar panels in future.